2017
DOI: 10.1016/j.vaccine.2016.09.053
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of durable immune responses six months after the last vaccination in preventive HIV vaccine trials

Abstract: Background The evaluation of durable immune responses is important in HIV vaccine research and development. The efficiency of such evaluation could be increased by incorporating predictors of the responses in the statistical analysis. In this paper, we investigated whether and how baseline demographic variables and immune responses measured two weeks after vaccination predicted durable immune responses measured six months later. Methods We included data from seven preventive HIV vaccine regimens evaluated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Additionally, durability of the immune response could be influenced by host-related factors such as antibody titers resulting from vaccination, host genetics (e.g., HLA type) [30], health history, and microbiome. For some biomarkers and for some vaccines, including those administered in the RV144 trial, 2-week post-vaccination responses predict durable responses 6 months later [31]. Our study of a heterologous prime-boost regimen demonstrates immune responses that vary considerably amongst individuals, suggesting that host factors contribute substantially to immune response durability.…”
Section: Discussionmentioning
confidence: 75%
“…Additionally, durability of the immune response could be influenced by host-related factors such as antibody titers resulting from vaccination, host genetics (e.g., HLA type) [30], health history, and microbiome. For some biomarkers and for some vaccines, including those administered in the RV144 trial, 2-week post-vaccination responses predict durable responses 6 months later [31]. Our study of a heterologous prime-boost regimen demonstrates immune responses that vary considerably amongst individuals, suggesting that host factors contribute substantially to immune response durability.…”
Section: Discussionmentioning
confidence: 75%
“…Env-specific CD8 +5 T cell response rates, though rarely detectable in both trials, when present, were significantly higher in HVTN 097 (P = 0.031) (table S1). HIV-1 Gag-specific CD4 + and CD8 + T cell response rates were very low and not statistically different between HVTN 097 (3.8%) and RV144 (2.5%), as demonstrated from samples derived from a cohort of uninfected RV144 vaccinees (n = 40) selected in 2010 (20). COMPASS analysis of the Env-specific CD4 + T cell single-cell functionality and polyfunctionality scores revealed that South African participants in HVTN 097 had a higher functionality score as compared to the Thai participants in RV144 (P = 0.038) (Fig.…”
Section: T Cell Responsesmentioning
confidence: 83%
“…By 6 months after second ALVAC/AIDSVAX vaccination (durability time point), the frequency of circulating 92TH023-Env specific CD4 + T cell responses among vaccine recipients in both studies had declined significantly when assessed by prevalence and magnitude; response rate dropped from 70.8 to 36.1% in HVTN 097 (P < 0.001, Table 2) and from 36.1 to 27.5% in the n = 40 uninfected vaccinees selected from RV144 samples in 2010 (P < 0.001) (20).…”
Section: T Cell Responsesmentioning
confidence: 94%
“…At the conclusion of the 3-year trial, the vaccine efficacy was 31.2% (2). Importantly, the RV144 trial identified multiple correlates for reduced risk of infection (3)(4)(5)(6). These include higher binding titers to an HIV envelope (Env) V1V2 scaffolded protein and antibody (Ab)dependent cellular cytotoxicity (ADCC) activity (3,4).…”
mentioning
confidence: 99%